Gambaran Pengetahuan dan Sanitasi terhadap Keberadaan Reservoar di Kelurahan Tandang - Yuniar Damayanti, Alfira; Martini, Martini; Hestiningsih, Retno; Yuliawati, Sri; Setiawan, Henry (Jurnal Riset Kesehatan Masyarakat, 2022)
Abstrak: Knowledge-based behavior generally lasts a long time. Knowledge is the result of knowing that occurs through sensory processes, especially the eyes and ears on certain objects. Knowledge is a very important domain for the formation of over-behavior. So that with sufficient knowledge, the person will try to live a clean and healthy life, as well as carry out routine health checks. This is related to community behavior that can worsen sanitation and lack of knowledge about preventing leptospirosis in the community which may increase the risk of being exposed to/infected with Leptospira bacteria so that the incidence of the disease occurs. Leptospirosis in society is getting higher. The incidence of leptospirosis is influenced by various factors that are closely related to behavior and the environment in humans. The high cases of leptospirosis in Semarang City are caused by poor sanitation conditions and the low level of public knowledge regarding leptospirosis. So it is necessary to describe the knowledge and sanitation of the existence of the reservoir in the Tandang Village. Based on the results obtained, the description of knowledge in Tandang Village is quite good. Meanwhile, sanitation in Tandang Village is classified as poor. Solution: Because people still don't care about the environment, there needs to be a movement from the authorities to invite the community to work together.